SEASONAL VARIATIONS IN SEMEN PRODUCTION OF MURRAH BUFFALO BULLS
Total of 4834 ejaculates collected from seven Murrah buffalo bulls were studied to observe the effect of seasons on semen quality, freezibility and loss of male gametes during frozen semen production. Mean values for seminal parameters viz. number of ejaculates per month, seminal volume ( ml), initial motility (% ), sperm concentration (106/ml), sperm output per ejaculate (million